Efek Pembukaan Lahan terhadap Karakteristik Biofisik Gambut pada Perkebunan Kelapa Sawit di Kabupaten Bengkalis - Suwondo, Suwondo; Sabiham, Supiandi; Sumardjo, Sumardjo; Paramudya, Bambang (Jurnal Natur Indonesia, 2012)
Oil palm plantations at peatland are faced with problems of land degraded, low productivity and produced to green house gas (GRG) emission.The objectives of this study were to land clearing effect of peatlands and to identified factors that affect the peatlands in the biophysicalcharacteristics. This study was conducted on District Bengkalis-Riau at marine and brakish peat. The data was collected using field survey anddocumentation. The descriptive analysis was used to determine biophysical characteristics and linier regresion was used to corelation performimportant factors. The research results showed that the biophysical characteristics of peatland experienced changes in the horizon profile,peat thickness, decomposition level, moisture content, ash content, pH, C-organic and biomass. The secondary peat swamp forest ofbiophysical characteristics have to different in the horizon profile, peat thickness, decomposition level, moisture content, ash content, pH,C-organic and biomass compared with marine and brackish peat.